The Alignment Challenges of Development Planning and Budgeting: Insights from Indonesia - Suhartono, Suhartono; Salomo, Roy Valiant; Prasetyo, Umanto Eko (Technium Social Sciences Journal, 2022)
This article examines the alignment challenges between development planning (DP) and public budgeting (PB), drawing on the Indonesian experience. DP is a policy tool to cover substantive policy, but its alignment with PB has received less attention in recent studies of public administration. We investigate the context of institutional choices and their implications for dynamic inside governance using qualitative methods and data analysis from in-depth interviews and data observation with those involved in law-making and institutional building of DP and PB. The findings conclude that the difference in reform reference and institutional rivalry has resulted in the separation of governance between DP and PB. This choice of governance raises issues of policy goals and budget alignment. Furthermore, this article discusses broader lessons on institutionalization, influential factors, and differentiation functions.